Post-translational modulation of cell signalling through protein succinylation - Katharina F. Kubatzky; Yue Gao; Dayoung Yu (Open Exploration Publishing Inc., 2023)
Cells need to adapt their activities to extra- and intracellular signalling cues. To translate a received extracellular signal, cells have specific receptors that transmit the signal to downstream proteins so that it can reach the nucleus to initiate or repress gene transcription. Post-translational modifications (PTMs) of proteins are reversible or irreversible chemical modifications that help to further modulate protein activity. The most commonly observed PTMs are the phosphorylation of serine, threonine, and tyrosine residues, followed by acetylation, glycosylation, and amidation. In addition to PTMs that involve the modification of a certain amino acid (phosphorylation, hydrophobic groups for membrane localisation, or chemical groups like acylation), or the conjugation of peptides (SUMOylation, NEDDylation), structural changes such as the formation of disulphide bridge, protein cleavage or splicing can also be classified as PTMs. Recently, it was discovered that metabolites from the tricarboxylic acid (TCA) cycle are not only intermediates that support cellular metabolism but can also modify lysine residues. This has been shown for acetate, succinate, and lactate, among others. Due to the importance of mitochondria for the overall fitness of organisms, the regulatory function of such PTMs is critical for protection from aging, neurodegeneration, or cardiovascular disease. Cancer cells and activated immune cells display a phenotype of accelerated metabolic activity known as the Warburg effect. This metabolic state is characterised by enhanced glycolysis, the use of the pentose phosphate pathway as well as a disruption of the TCA cycle, ultimately causing the accumulation of metabolites like citrate, succinate, and malate. Succinate can then serve as a signalling molecule by directly interacting with proteins, by binding to its G protein-coupled receptor 91 (GPR91) and by post-translationally modifying proteins through succinylation of lysine residues, respectively. This review is focus on the process of protein succinylation and its importance in health and disease.